Continuous Light-Induced PCOS-Like Changes in Reproduction, Metabolism, and Gut Microbiota in Sprague-Dawley Rats - Chu, Weiwei; Zhai, Junyu; Xu, Jieying; Li, Shang; Li, Weiping; Chen, Zi-Jiang; Du, Yanzhi (Frontiers in Microbiology, 2020)
The interplay between genetic and environmental risk factors contributes to the pathogenesis of metabolic disease. Polycystic ovary syndrome (PCOS) is the most common endocrine and metabolic disorder in women of reproductive age. Circadian rhythm disruption is an important risk factor for PCOS. In this study, we evaluated the effect of circadian disorder on reproduction as well as metabolism, and determined its influence on gut microbiota in a rat model. Female Sprague Dawley rats were kept under continuous light exposure (12-h:12-h light/light cycle, L/L group) or a control cycle (12-h:12-h light/dark cycle, L/D group) for four consecutive weeks. Manifestations in endocrine hormones and metabolism were detected and gut microbiota were analyzed with the 16s rRNA gene sequencing technique. To our knowledge, this is the first study to report PCOS-like reproductive manifestation, such as anti-Müllerian hormone (AMH) elevation induced by continuous light exposure. Moreover, continuous light resulted in abnormal glucose metabolism and gut microbial community variations, including enrichment of the microbial genus of Parasutterella and reduced abundance of genus Corynebacterium, genus Odoribacter, and genus Acinetobacter. Increased Parasutterella abundance was positively correlated with serum testosterone level. A PICRUSt analysis revealed that reproductive and metabolic-related genes were enriched in rats of L/D group. In conclusion, the present study demonstrates that continuous light exposure, an important environmental factor, contributes to the occurrence and developmental progress of PCOS and changes in microbial component and structure. Continuous light exposure is one of vital causes of PCOS, which is closely related to microbial structure and functions.